2010
DOI: 10.1111/j.1741-3729.2010.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Families Manage Their Economic Hardship?

Abstract: Using data from the 2007 Survey of Consumer Finances, this study examined how families manage their economic hardship. A conceptual model was developed based on risk management theory and the permanent income hypothesis. About half of families used credit and about a third used their own savings to make up the difference between income and spending. The results of multinomial logit analysis showed that families' use of management methods differed when they faced economic hardship, depending on their situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…That is, couples experiencing economic difficulties will either utilize lines of credit or spend down their savings to maintain the lifestyle to which they are accustomed. In line with these predictions, studies based on pre-recession data have shown that couples may turn to lines of consumer credit or may use liquid savings to maintain their standard of living when facing economic difficulties (Baek & DeVaney, 2010 Hypothesis 1: Reported financial declines and feelings of economic pressure are negatively associated with reports of sound financial management behavior (see Figure 1). …”
Section: Financial Declines and Financial Management Behaviormentioning
confidence: 67%
See 1 more Smart Citation
“…That is, couples experiencing economic difficulties will either utilize lines of credit or spend down their savings to maintain the lifestyle to which they are accustomed. In line with these predictions, studies based on pre-recession data have shown that couples may turn to lines of consumer credit or may use liquid savings to maintain their standard of living when facing economic difficulties (Baek & DeVaney, 2010 Hypothesis 1: Reported financial declines and feelings of economic pressure are negatively associated with reports of sound financial management behavior (see Figure 1). …”
Section: Financial Declines and Financial Management Behaviormentioning
confidence: 67%
“…Alternatively, families may increasingly rely on consumer debt to maintain their standard of living (Baek & DeVaney, 2010). Reducing sound financial management behaviors may free up additional funds for families in the short term, but it may be financially problematic for them in the long term.…”
mentioning
confidence: 99%
“…Research conducted since the [2007][2008][2009] Recession found that couples strived to positively cope with the challenges of unemployment by engaging in wise financial behaviors (Baek & DeVaney, 2010). There was also a documented increase in wives' labor force participation during the recession (Mattingly & Smith, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The studies we received in response were novel and timely. Two examples are a study that examined whether the recession pulled more wives into the labor force (Mattingly & Smith, 2010) and another that examined the predictors of using savings or consumer debt during a shortfall in income (Baek & DeVaney, 2010). The studies in this category provide insight into how families have dealt with (and are still dealing with) the effects of the recession.…”
mentioning
confidence: 99%